1998
DOI: 10.1016/s1054-139x(98)00033-0
|View full text |Cite
|
Sign up to set email alerts
|

Substance use and risky sexual behavior among homeless and runaway youth

Abstract: Purpose-To (a) characterize human immunodeficiency virus (HIV)-related risk behaviors of homeless youth; (b) determine whether substance use is associated with risky sexual behavior in this population; and, if so, (c) explore explanations for this relationship.Methods-A purposive sample of 327 homeless youth (ages 14-21 years) in Washington, DC, were surveyed in 1995 and 1996. Survey items were adapted from items used in a national study of adult substance use and sexual behavior and measured global (lifetime)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
136
1
18

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(164 citation statements)
references
References 20 publications
9
136
1
18
Order By: Relevance
“…The reasons for these findings are unclear. They contrast with findings from the general population and among homeless youth, where having multiple sexual partners has been shown to be associated with greater risktaking behaviors, including contraceptive nonuse [19,20]. This discrepancy may be because homeless women who are married or living with partners and those in monogamous relationships may be less averse to becoming pregnant than those who have multiple partners and no committed relationship.…”
Section: Discussioncontrasting
confidence: 74%
See 1 more Smart Citation
“…The reasons for these findings are unclear. They contrast with findings from the general population and among homeless youth, where having multiple sexual partners has been shown to be associated with greater risktaking behaviors, including contraceptive nonuse [19,20]. This discrepancy may be because homeless women who are married or living with partners and those in monogamous relationships may be less averse to becoming pregnant than those who have multiple partners and no committed relationship.…”
Section: Discussioncontrasting
confidence: 74%
“…The homeless women in this study reported high rates of contraceptive nonuse or rare use despite their risk for unintended pregnancy [19][20][21]. One-third of sexually-active homeless women at risk for unintended pregnancy were not using contraception, or did so only rarely; one in four (27%) were not using any form of contraception at all, compared to 5% in the general population [8].…”
Section: Discussionmentioning
confidence: 70%
“…Using data from a national survey, Schafer, Blanchard & Fals-Stewart (1994) found that people who used any drug (not including alcohol) at the most recent sexual encounter with a new sexual partner were less likely to use condoms than were non-users. Street youth who used marijuana in a recent sexual encounter were less likely to use condoms, but those who used crack were more likely to use condoms (Bailey, Camlin, and Ennett, 1998). Marijuana use with sex was also associated with decreased condom use at a recent sexual encounter among adolescents in detention (Kingree and Betz, 2003;Kingree, Braithwaite, and Woodring, 2000;Kingree and Phan, 2002) and among MSM (Clutterbuck et al, 2001), but was unrelated to condom use among young heterosexual adults (Brodbeck, Matter, and Moggi, 2006).…”
Section: Introductionmentioning
confidence: 95%
“…[3][4][5] Additionally, the time spent on the street exposes them to drug users, sexual predators and other high-risk individuals who may exploit them and endanger their physical health. 6,7 Also, homeless youth have extremely low rates of condom usage and numerous sexual partners, 6,[8][9][10][11][12] which increases their risk for contracting STI. Self-reported rates of STI among homeless youth range from ~20% to 37%.…”
Section: Introductionmentioning
confidence: 99%